HUBUNGAN SIKAP IBU HAMIL DENGAN PERILAKU DIET SELAMA HAMIL - Nur, Fadjri Nilakesuma; Susilawati, Dewi (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
Maternal nutritional status during pregnancy is an aspect that supports optimal growth and development of the fetus. WHO says 40% of maternal deaths in developing countries are caused by KEK and anemia during pregnancy. Pregnant women who have malnutrition greatly affect the state of health, fetal development and adversely affect pregnancy outcomes. The nutritional status of pregnant women is influenced by many factors, including internal factors such as knowledge, attitude, dietary behavior. The purpose of this study was to see whether there is a relationship between attitude and dietary behavior during pregnancy. This type of research was a descriptive analytic with cross sectional design. The research sample was 100 pregnant women who visited the Independent Practicing Midwives in Padang City in July - August 2021. Data processing were carried out by editing, coding, data entry and tabulation. The research was analyzed by chi-square. Based on the results of the study, it was found that there was a relationship between attitude and dietary behavior during pregnancy (p value 0.002). Therefore, the attitude of pregnant women greatly determines the dietary behavior of pregnant women in fulfilling nutrition during pregnancy.